Choroidal nevi in adult Indians: the central India eye and medical study - Nangia, Vinay; Jonas, Jost B. (British journal of ophthalmology, 2012)
A choroidal nevus is a melanocytic choroidal lesion which is less than 5 mm in its largest basal diameter and smaller than 1 mm in its height.1 The clinical importance of choroidal nevi relates to their potential malignant transformation and reported association with visual impairment.2 The reported prevalence of choroidal nevi varies from 0.2% to 30%.3 ,4 Since most data on the prevalence of choroidal nevi did not originate from population-based studies, and because population-based data have not been available particularly for the Indian population, it was the purpose of our study to determine the frequency of choroidal nevi and their associations in a population-based investigation in India. The Central India Eye and Medical Study is a population based cross sectional study performed in rural Central India.5 The Medical Ethics Committee of the Medical Faculty Mannheim …
Gesehen am 23.05.2018